Investigation of the effects of extraction temperature and time on bioactive compounds content from garlic (Allium sativum L.) husk - Thach, Nguyen Ai (Frontiers in Sustainable Food Systems, 2022)
Garlic (Allium sativum L.) has been used as a functional food and medicine in traditional prescriptions for centuries. The extract of garlic husks contains phytonutrients and antioxidant capacity, which can be applied in the food, nutraceutical, cosmetics, and pharmaceutical industries. However, garlic husks, a by-product of the food industry, are considered agricultural wastes. Hence, this research aims at evaluating the content of several compounds in the extract of garlic husks and determining the appropriate temperature and time for the extraction processing of bioactive compounds from garlic husks. In this research, garlic husk powder was extracted at different temperatures from 40 to 80oC during time durations of 30–120 min. This study found that the optimum temperature was from 60 to 70oC and the time duration was from 60 to 90 min for the extraction process. The optimal content of total polyphenols content of 8.93 ± 0.252 mg gallic acid equivalent/g, total flavonoids content of 0.028 ± 0.002 (mg quercetin equivalent/g), total thiosulfinates content of 9.73 ± 0.071 (μmol/g), and total anthocyanins content of 0.0047 ± 0.0001 (mg/g) of dried garlic husk. Based on the finding, the study suggests that garlic husk should be utilized as a potential source of natural antioxidants in garlic extract, a food supplement, that contains antioxidants to support the cardiovascular and immune systems+ and odorless garlic products.